Symposium 1: Challenges and possibilities for Design Based Research with semantic web technology - Jensen, Jesper; Dohn, Nina Bonderup (Proceedings of the International Conference on Networked Learning, 2016)
This paper addresses the first conference theme of Theories, methodologies, perspectives and paradigms for Research in Networked Learning. The three key themes of the symposium (Designs for learning with the Semantic Web) are discussed by exploring the methodological challenges and advantages that one may experience when conducting design based research with emergent technology. In particular, when technological solutions are developed more or less from scratch, simultaneously and in interaction with the pedagogical practices which make use of these solutions. The outset for this paper is a Design Based Research (DBR) project, which we are currently carrying out at a Danish high school. The project involves development of technological tools based on semantic web (web 3.0) technology. These tools are developed simultaneously and in interaction with the pedagogical practices utilizing the tools. We seek to address the aforementioned main question of the paper by, first, reviewing the stages of DBR-processes as presented by Amiel & Reeves (2008), second, presenting the specific DBR project which is our outset, and third presenting a set of methodological challenges and advantages we have experienced in our work on this project. Through the discussion presented in this paper, we draw attention to several noteworthy challenges and advantages of developing and utilizing emergent-technology-based tools in DBR. Some of these challenges concern the potentially intangible nature of emergent technology and the difficulty of communicating the potentials of the technology to practitioners and other involved parties. Other challenges are more strongly connected with the practical development process. Similarly, we explore noteworthy advantages such as emergent technology potentially granting a greater level of creative freedom in development of solutions and tools while greatly encouraging teacher and student involvement in the development process. This further provides an opportunity for a stronger focus on designing with practice in mind. In addition, the paper argues that DBR projects like the one described in this paper, are actually paradigmatic for investigation of educational contexts in rapid technological and pedagogical change because they not only take this change into account, but fundamentally and significantly build on them.